2021
DOI: 10.1186/s11658-021-00269-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DNM3OS regulates GREM2 via miR-127-5p to suppress early chondrogenic differentiation of rat mesenchymal stem cells under hypoxic conditions

Abstract: Background Improved chondrogenic differentiation of mesenchymal stem cells (MSCs) by genetic regulation is a potential method for regenerating articular cartilage. MiR-127-5p has been reported to promote cartilage differentiation of rat bone marrow MSCs (rMSCs); however, the regulatory mechanisms underlying hypoxia-stimulated chondrogenic differentiation remain unknown. Methods rMSCs were induced to undergo chondrogenic differentiation under normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These data showed that miR-127-5p might exert a regulative role on osteogenesis by modulating multiple pathways. In line with this hypothesis, several negative regulators of osteogenesis has been identified as the target for miR-127-5p, like Gremlin2 [ 26 ], which is a bone morphogenetic protein antagonists and suppresses osteogenesis in BMSCs [ 27 ], and PTEN [ 25 ]. Further study is warranted to reveal other mechanisms underlying the regulation of miR-127-5p in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that miR-127-5p might exert a regulative role on osteogenesis by modulating multiple pathways. In line with this hypothesis, several negative regulators of osteogenesis has been identified as the target for miR-127-5p, like Gremlin2 [ 26 ], which is a bone morphogenetic protein antagonists and suppresses osteogenesis in BMSCs [ 27 ], and PTEN [ 25 ]. Further study is warranted to reveal other mechanisms underlying the regulation of miR-127-5p in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The migration and viability of MSCs was promoted by P21 under in vitro hypoxic preconditioning (79). DNM3OS/miR-127-5p /GREM2 may be involved in hypoxic chondrocyte differentiation (95). H19 enhanced the survival rate and angiogenesis potential of BMSCs in vitro.…”
Section: Hypoxia Induced Ncrnas With a Role In The Fate Of Mscsmentioning
confidence: 95%
“…Rat MSCs have been widely explored due to their capability to regenerate and differentiate to more specialized cells, including bone cells (osteocytes), fat cells (adipocytes) and cartilage cells (chondrocytes) [140]. Bone marrow highly enables the isolation of these cells, which is mostly obtained from rat femur and tibia parts [141].…”
Section: Graphene Oxide In Rat Mesenchymal Stem Cellsmentioning
confidence: 99%